Farming's climate-smart future: placing agriculture at the heart of climate-change policy - Pye-Smith, Charlie (CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the Technical Centre for Agricultural and Rural Cooperation (CTA), 2011)
Containing a wealth of up-to-date research and examples, this booklet highlights the ‘cause and effect’ relationship between agriculture and climate change. Crucially it observes that a range of practices – ‘climate-smart agriculture’ – could increase food production, help farmers to become more resilient to global warming and reduce emissions of greenhouse gases. Yet how widespread these practices become will depend on the importance given to agriculture in international climate change negotiations and national policy-making. The first chapter examines how farming contributes to human-generated greenhouse gas emissions, and observes the effects of global warming and its impact on agriculture and fisheries. Chapter 2 considers possible solutions: adaption and mitigation strategies that farmers and fishers may adopt. Examples include conservation agriculture, agroforestry and climate-smart livestock farming. Boosting the role of agriculture in climate change negotiations – by establishing a work programme and setting up pilot projects – is addressed in chapter 3, while chapter 4 briefly reflects on the financial implications of adapting to climate change in the agricultural sector.